Seguimiento farmacoterapéutico a pacientes con diabetes mellitus tipo 2 del Centro de Salud I-4 Nauta - Raygada-Ramirez, Patricia (2022)
Diabetes mellitus is a chronic disease that is increasing worldwide and in Peru; so that patients suffering from this disease may present problems related to medications. The objective of this research was to provide a Pharmacotherapeutic Follow-up (SFT) service to older adult patients diagnosed with type 2 diabetes mellitus; at the same time identify the type of problems and the causes that generate the Problems Related to Medications (PRM); as well as pharmaceutical intervention (FI) and pharmacotherapeutic compliance of patients for prevention. It is a prospective, descriptive, and longitudinal study. Using the tools of the Dáder methodology to carry out pharmacotherapeutic follow-up (SFT), the evaluation of compliance and knowledge was carried out using the Morisky-Green test; Patients with type 2 diabetes mellitus, who were treated at the I-4 Nauta Health Center, were evaluated for three months. 13 patients were included in the study. In total, 13 drug-related problems (DRPs) were detected, with 1 DRP (53.8%) being the most frequent, followed by 4 DRPs (15.4%). Inadequate conservation (23.1%) and non-compliance with treatment (30.8%) were identified as the most frequent causes. Through the SFT, the type and causes that generate drug-related problems (PRM) were identified, and at the same time it was observed that 61.5% corresponded to need, 23.1% to effectiveness, and 15.4% to safety. It was concluded that the optimization of the SFT is positively influenced in the improvement of the patient’s health status.